Performance Analysis of Small-Scale Educational Solar Photovoltaic Modules Based on Irradiation Variations and Environmental Temperature in Cimahi City - Ridwan Nurdin; Sri Paryanto Mursid; Sri Utami; Muhamad Irfan Nurdin; Sofy Fitriani (Journal of Electrical Vocational Education and Technology, 2026)
Abstract This study aims to evaluate the operational characteristics of a 50 Wp polycrystalline photovoltaic (PV) module under actual environmental conditions as a basis for developing renewable energy practicum media. The research method was carried out through field testing in Cimahi City with parameters including solar irradiation, panel temperature, and electrical parameters (voltage, current, and power) recorded at five-minute intervals. The results of data analysis showed a strong correlation between irradiation intensity and output power, with a coefficient of determination (R²) of 0.93. The results showed that output power increased with increasing irradiation, while increasing panel temperature decreased output voltage. Panel efficiency was in the range of 9.2%-13.1%, lower than manufacturer specifications due to non-STC environmental conditions and system losses. Nevertheless, the PV module proved effective as a project-based learning medium that was able to provide students with a practical understanding of the influence of environmental factors on the performance of photovoltaic systems. Abstrak Penelitian ini bertujuan untuk mengevaluasi karakteristik operasional modul fotovoltaik (PV) polikristal 50 Wp pada kondisi lingkungan aktual sebagai dasar pengembangan media praktikum energi terbarukan. Metode penelitian dilakukan melalui pengujian lapangan di Kota Cimahi dengan parameter yang meliputi iradiasi matahari, suhu panel, serta parameter listrik (tegangan, arus, dan daya) yang direkam pada interval lima menit. Hasil analisis data menunjukkan adanya korelasi yang kuat antara intensitas iradiasi dan daya keluaran, dengan koefisien determinasi (R²) sebesar 0,93. Hasil penelitian menunjukkan bahwa daya keluaran meningkat seiring dengan bertambahnya iradiasi, sedangkan kenaikan suhu panel menurunkan tegangan keluaran. Efisiensi panel berada pada rentang 9,2%–13,1%, lebih rendah dari spesifikasi pabrikan akibat kondisi lingkungan yang tidak sesuai dengan STC (Standard Test Conditions) serta adanya rugi-rugi sistem. Meskipun demikian, modul PV terbukti efektif sebagai media pembelajaran berbasis proyek yang mampu memberikan pemahaman praktis kepada mahasiswa mengenai pengaruh faktor lingkungan terhadap kinerja sistem fotovoltaik.